INFLUENCE DEMOGRAPHIC FACTORS ON THE FINANCIAL CONDITION PENSION SYSTEM OF UKRAINE IN MODERN CONDITIONS - Rudyk , V.K. (The actual problems of regional economy development, 2016)
We consider the impact of demographic processes in Ukraine need to reform the national pension system. Analyzes trends in the demographic field over the past decade, characterized by its main indicators studied their effect on income retirement age. Particular attention is paid to population pressure in the pension system of Ukraine for the past ten years, is considered the ratio between working age citizens and pensioners, as it affects the financing of the pension sector, investigated the replacement rate changes over the period. The assessment of the financial condition of the national pension system through key indicators that allow you to make relevant conclusions on further pension reform in Ukraine. JEL: H 55